Artificial Intelligent Opportunities for Creativity and Innovation of Future Radio Translators - Harliantara Harliantara (Jurnal Syntax Transformation, 2024)
Radio broadcasting is an industry where creativity and innovation can be significantly influenced by Artificial Intelligence (AI), which can generate many ideas quickly, help the design process and inspire human creativity. This research aims to acquire factual knowledge revealing the important aspects that arise in Artificial Intelligence (AI). This research uses a qualitative descriptive method with a literature study approach. The findings show that AI can assist in content creation, listener preference analysis, and broadcast schedule optimization. It is important to note that AI cannot replace human wisdom and creativity, but can be used as a tool to enhance and complement human capabilities, making content creation and broadcasting more efficient and successful.